External genital abnormalities in male primary school children: importance of structured school health survey - Gupta, Alok; Singh, Rajendra P. (International Journal Of Community Medicine And Public Health, 2020)
Background: Abnormalities of external genitalia are often under diagnosed in early childhood because of lack of awareness of parents about the anatomy of external genitalia and social inhibitions. These abnormalities, if left untreated, may lead to psychological, social, and sexual complication. Structured school health survey and awareness among parents can identify these abnormalities at early stage to avoid further complications later. Study was aimed at spreading awareness among parents of young children and school administration about importance of structured screening programme for detecting external genital abnormalities among the young boys to avoid various related complications later. Methods: It was a cross-sectional study covering 586 male primary school children of class I to V aged 6-12 yrs of two Schools in a capital city in northern state of India. All participants were physically examined for external genital anomalies by a trained medical officer. Data collected were analysed using standard statistical software, Statistical Programme for Social Sciences (SPSS) 15.0. Results: Abnormalities were detected in 84 (14.33%) children. Phimosis was commonest abnormality (7.5%), followed by Inguinal Hernia, Un-descended Testes, Hypospadias, Varicocele and Hydrocele. Children of parents having higher educational level were found having lesser prevalence of abnormalities. Conclusions: Diagnosis and management of abnormalities of external genitals of children is delayed due to lack of awareness among parents. Careful screening of these abnormalities at pre-school and school age, increased public awareness and early referral of children is very important to avoid the risk of having urogenital complications during adulthood.